Dupilumab and COVID‐19: What should we expect?. Issue 4 (20th May 2020) - Patruno, Cataldo; Stingeni, Luca; Fabbrocini, Gabriella; Hansel, Katharina; Napolitano, Maddalena
Abstract: Coronavirus disease 2019 (COVID‐19) is a pandemic disease caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) with high morbidity and mortality. There are very limited data on the interference of immunomodulating drugs on the risk of infection and on the course of the disease. In particular, there are no current clinical data about the interference exerted by dupilumab, a biologic drugs blocking IL‐4 and IL‐13, used for adult atopic dermatitis. The pathogenesis of COVID‐19 is complex, characterized by an immune response mainly Th1/Th17. The hyper‐activation of these cells may cause the release of pro‐inflammatory cytokines that may result in lung impairment. IL‐4 and IL‐13 are Th2 cytokines, thus being part of a pathway not considered implicated in host defense mechanism against viral infections. Indeed, viral infections, including respiratory infections, have not been reported as a significant adverse event in clinical trials. Furthermore, dupilumab has been proved to be efficacious also in exacerbations of asthma, and it is known that viral infections can worsen asthma. Therefore, the current data seem to suggest that treatment with dupilumab should not be stopped during COVID‐19 pandemic. Obviously, a careful assessment is mandatory for each individual patient and further studies are necessary to characterize the immunologic responses in COVID‐19.